Ferritin Contains Less Iron ((59)Fe) in Cells When the Protein Pores Are Unfolded by Mutation - Hasan, Mohammad R. (American Society for Biochemistry and Molecular Biology, 2008)
Ferric minerals in ferritins are protected from cytoplasmic reductants and Fe(2+) release by the protein nanocage until iron need is signaled. Deletion of ferritin genes is lethal; two critical ferritin functions are concentrating iron and oxidant protection (consuming cytoplasmic iron and oxygen in the mineral). In solution, opening/closing (gating) of eight ferritin protein pores controls reactions between external reductant and the ferritin mineral; pore gating is altered by mutation, low heat, and physiological urea (1 mm) and monitored by CD spectroscopy, protein crystallography, and Fe(2+) release rates. To study the effects of a ferritin pore gating mutation in living cells, we cloned/expressed human ferritin H and H L138P, homologous to the frog open pore model that was unexpressable in human cells. Human ferritin H L138P behaved like the open pore ferritin model in vitro as follows: (i) normal protein cage assembly and mineralization, (ii) increased iron release (t(½) decreased 17-fold), and (iii) decreased α-helix (8%). Overexpression (>4-fold), in HeLa cells, showed for ferritin H L138P equal protein expression and total cell (59)Fe but increased chelatable iron, 16%, p < 0.01 ((59)Fe in the deferoxamine-containing medium), and decreased (59)Fe in ferritin, 28%, p < 0.01, compared with wild type. The coincidence of decreased (59)Fe in open pore ferritin with increased chelatable (59)Fe in cells expressing the ferritin open pore mutation suggests that ferritin pore gating influences to the amount of iron ((59)Fe) in ferritin in vivo.